2011
DOI: 10.1016/j.dsr2.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of macrofaunal assemblages from three Portuguese submarine canyons (NE Atlantic)

Abstract: a b s t r a c tThe macrofaunal assemblages from three Portuguese submarine canyons, Nazaré , Cascais and Setú bal were studied from samples collected at their upper (900-1000 m), middle (3200-3500 m) and lower sections (4200-4500 m) and at the adjacent open slopes ( $ 1000 m), during the HERMES cruises D297 (R.R.S. Discovery, 2005) CD179 (R.R.S. Charles Darwin, 2006) and 64PE252 (R.V. Pelagia, 2006). The taxonomic composition and patterns in biodiversity, abundance and community structure of the benthic macrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 84 publications
(137 reference statements)
7
59
0
Order By: Relevance
“…Abundances recorded in the present study were comparable with those observed by Cunha et al (2011) Witte et al, 2003a;Sweetman and Witte, 2008b). Benthic macrofaunal assemblages exhibited conspicuous differences between the Whittard canyons eastern and western branches.…”
Section: Macrofaunal Assemblagessupporting
confidence: 75%
See 1 more Smart Citation
“…Abundances recorded in the present study were comparable with those observed by Cunha et al (2011) Witte et al, 2003a;Sweetman and Witte, 2008b). Benthic macrofaunal assemblages exhibited conspicuous differences between the Whittard canyons eastern and western branches.…”
Section: Macrofaunal Assemblagessupporting
confidence: 75%
“…Canyon sediments receive increased POM inputs via both vertical transport, through the water column, and lateral transport, through slope processes. Consequently, canyons may support higher bacterial and faunal densities than surrounding bathyal and abyssal sediments (Vetter and Dayton, 1998;Duineveld et al, 2001;EscobarBriones et al, 2008;De Leo et al, 2010;Cunha et al, 2011). In the Whittard Canyon (Northeast Atlantic), Duineveld et al (2001) report enhanced sediment community oxygen consumption (SCOC) within canyon sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Such trophic characteristics allow us to hypothesize, according to the optimal foraging theory (McArthur and Pianka, 1966), that benthic detritus feeders inhabiting the Nazarè canyon may have relevant energetic/metabolic advantages compared to those inhabiting the open slopes. These findings provide additional support to explain why higher meiofaunal and macrofaunal standing stocks are reported in the Nazarè canyon compared with the adjacent open slopes at similar depths (Ingels et al, 2009;Cunha et al, 2011). Moreover, the enhanced nutritional value of bioavailable organic detritus with increasing water depth can contribute, along with other factors previously suggested (e.g., level of physical disturbance and spatial heterogeneity), to justify the distribution patterns of macrofaunal abundances, i.e.…”
Section: Discussionsupporting
confidence: 55%
“…Allen et al 2001, Ryan et al 2005 and subsequent distribution and diversity of higher trophic levels (Cunha et al 2011, Fanelli et al 2011. Canyon dynamics along some regions of the Antarctic continental margin may be affected both by latitudinal trends in atmospheric warming and sea ice loss, as well as regional shifts in winds and ocean circulation.…”
Section: Introductionmentioning
confidence: 99%